FUNGSI MANAJEMEN PUBLIC RELATIONS PADA KAMPANYE POLITIK - Damayanti, Novita (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
Presidential election is part of democracy system in Indonesia. The backbone of political campaign for election is found within power of communication. Public relations are Â the tool of political campaign that have manageÂ ment function such as: researching, planning, implementing and evaluating an array of communication activities. Frame political public relations in political campaign are : image management, information management, media management, and internal communication.